Strip-shaped ortho-parahydrogen conversion catalyst and preparation method thereof
By using a strip-shaped secondary hydrogen conversion catalyst prepared by weak crystalline hydrated iron oxide and clay, the problems of low specific surface area and insufficient strength of the existing catalyst are solved, and an efficient secondary hydrogen conversion reaction is achieved, which is suitable for high aerial speed conditions.
Patent Information
- Application Number
- CN202310938189.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-28
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2043-07-28
AI Technical Summary
The existing secondary hydrogen conversion catalysts have low specific surface area and insufficient particle strength, resulting in large wear and low synthesis efficiency, and are not suitable for catalytic reactions under high airspeed conditions.
A strip-shaped secondary hydrogen conversion catalyst was prepared by weak crystalline hydrated iron oxide and clay, and catalyst particles with high specific surface area and high physical strength were formed through ultrasonic dispersion and mechanical dispersion.
It improves the specific surface area and physical strength of the catalyst, reduces wear, enhances the preparation efficiency of the catalyst, and is suitable for normal secondary hydrogen conversion reactions under high aerial speed conditions, with a conversion rate of 90~98%.
Smart Images

Figure CN119425694A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of catalytic conversion of normal para-hydrogen and relates to a strip-shaped normal para-hydrogen conversion catalyst and a preparation method thereof. Background Art
[0002] Liquid hydrogen is a highly efficient liquid fuel with broad application prospects in chemical production, aerospace engineering, hydrogen-powered vehicles, etc. Liquid hydrogen has the advantages of being easy to store and measure, and has become one of the important ways to use, store and transport hydrogen energy.
[0003] A hydrogen molecule is composed of two hydrogen atoms with different nuclear spin directions, of which orthohydrogen is symmetrical and parahydrogen is antisymmetric. Both orthohydrogen and parahydrogen can exist stably in liquid and gaseous states, and their equilibrium concentrations are affected by temperature. At room temperature, the orthohydrogen content in hydrogen is 25% and the parahydrogen content is 75%, which is called normal hydrogen or standard hydrogen. When the temperature drops, orthohydrogen will spontaneously convert to parahydrogen. At the standard boiling point of liquid hydrogen, the parahydrogen content can reach 99.8%. In the absence of an external catalyst, the spontaneous conversion of the orthohydrogen to the parahydrogen state is very slow, and the heat released during the conversion process is greater than the vaporization heat of liquid hydrogen, which will cause vaporization loss of liquid hydrogen. In order to quickly complete the conversion of orthohydrogen to parahydrogen while liquefying hydrogen, the development of high-performance orthohydrogen conversion catalysts is crucial for the production of liquid hydrogen.
[0004] Currently, amorphous hydrated iron oxide is mainly used as a catalyst for the conversion of ortho-parahydrogen.
[0005] CN202111354244.6 discloses a method for preparing a doped ortho-parahydrogen conversion catalyst. An iron salt solution and a metal ion solution to be doped are prepared separately, and the metal ion solution to be doped is dripped into the iron salt solution in a certain proportion, and then an appropriate amount of alkali solution is added. The precipitate obtained by hydrothermal reaction of the mixed solution is washed, dried, and ground to obtain irregularly shaped hydrated iron oxide particles. The particles have more edges and corners, lower strength, and greater wear when used as a catalyst. On the other hand, the doped iron oxide prepared by the method using a high-temperature hydrothermal method has a larger grain size (300~1000nm), a high product crystallinity, and a small specific surface area. At the same time, the high-temperature reaction time used is too long, the synthesis efficiency is low, and the energy consumption is high.
[0006] CN202210832769.4 provides a catalyst for the conversion of ortho-parahydrogen and a preparation method thereof. The catalyst is a fiber magnetic catalyst FeMnO doped with Fe atoms. x , having a fibrous structure with a diameter of 2 to 5 nm and a length of 100 nm to 500 nm, a large product particle size and a low specific surface area. This method requires the use of a hydrothermal reaction, which consumes a lot of energy, and because a manganese oxide precursor needs to be prepared, the preparation cost is also high.
[0007] CN201910782910.2 discloses a method for preparing hydrated iron oxide, adding a weakly basic compound to a ferric chloride solution, aging, filtering, and dispersing the filter cake in an ammonium bicarbonate solution, filtering, and drying to obtain hydrated iron oxide. The method uses a weak base as a precipitant, and the crystalline phase of the product obtained by the reaction at room temperature and pressure is mainly amorphous. The method reacts the filter cake with ammonium bicarbonate, and then uses the pore-forming effect of ammonium bicarbonate pyrolysis to increase the specific surface area of the product, but it will cause a significant decrease in the strength of the dried particles, and the particles have more edges and corners, resulting in greater wear.
[0008] [Progress in Fine Petrochemicals, 2010, 11 (7): 26-31] The effect of the order of adding the two materials, iron salt and alkali, on the properties of the iron hydroxide product was investigated. It was found that the specific surface area of the product obtained by adding the iron salt solution to the alkali solution and the alkali solution to the iron salt solution was larger than the latter, but overall the specific surface areas of both were small, and the products obtained were all amorphous crystals.
[0009] [Journal of Research of the National Bureau of Standards, 1958, 60 (3): 221-227] The study found that when hydrated iron oxide is used for the conversion of para-hydrogen, the catalyst particle size is better when it is 20-50 mesh. However, due to the small size of the catalyst particles, it is easy to clog the bed and is not suitable for catalytic reactions at high space velocities, making it difficult to improve the efficiency of para-hydrogen preparation.
[0010] Specific surface area, particle size, particle strength and abrasion are important control indicators of catalytic materials. The hydrated iron oxide used in the above-mentioned para-hydrogen conversion catalysis has a low specific surface area or weak particle strength, which is not conducive to improving the performance of the para-hydrogen catalyst. Summary of the invention
[0011] In view of the shortcomings of the prior art, the present invention provides a strip-shaped para-hydrogen conversion catalyst and a preparation method thereof. The para-hydrogen conversion catalyst of the present invention has a large specific surface area, high physical strength, a simple preparation method, few catalyst particles, low energy consumption, high preparation efficiency, and is suitable for para-hydrogen conversion reactions under high space velocity conditions.
[0012] The strip-shaped normal-parahydrogen conversion catalyst of the present invention comprises weakly crystalline hydrated iron oxide and clay, wherein the weakly crystalline hydrated iron oxide accounts for 80% to 95% and the clay accounts for 5% to 20% based on the total weight of the catalyst; the microscopic particle size of the weakly crystalline hydrated iron oxide is 3 to 12 nm; the weakly crystalline hydrated iron oxide has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.
[0013] In the catalyst of the present invention, the radial size of the catalyst particles is 1.0-1.5 mm, the axial length is 1.5-4.5 mm, the radial crushing strength is 4.5-12.5 N / mm, and the abrasion is 0.10-0.25%. The specific surface area is 150-285 m 2 / g.
[0014] The preparation method of the strip-shaped normal-parahydrogen conversion catalyst of the present invention comprises the following contents: (1) Mixing the iron salt solution and the inorganic alkali solution under the simultaneous action of ultrasonic dispersion and mechanical dispersion to form a colloidal mixture, and then leaving the colloidal mixture to stand for 0.5-5 hours; (2) washing and separating the mixture of step (1) to obtain wet hydrated iron oxide having a water content of 25 wt% to 50 wt%; (3) The wet hydrated iron oxide obtained in step (2) is fully mixed with clay, and after kneading, extruding and drying, a strip-shaped normal-parahydrogen conversion catalyst is obtained.
[0015] In the method of the present invention, step (1) is generally carried out at room temperature, which generally refers to a temperature of 10 to 45°C.
[0016] In the method of the present invention, the iron salt in step (1) is ferric chloride and / or ferric sulfate; the iron salt solution in step (1) is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.
[0017] In the method of the present invention, the inorganic base in step (1) is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate, preferably sodium hydroxide or potassium hydroxide; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.
[0018] In the method of the present invention, the iron salt solution in step (1) is Fe 3+Calculate with inorganic alkali solution to OH - The molar ratio is 3.0 to 4.5.
[0019] In the method of the present invention, the ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 kHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.
[0020] In the method of the present invention, the mechanical dispersion in step (1) includes but is not limited to any method and operating conditions that are conducive to rapid and uniform mixing of the materials, such as mechanical stirring, magnetic stirring, shaking table, shear stirring, etc.
[0021] In the method of the present invention, the order and method of adding the materials in step (1) are not particularly limited, but preferably the alkali solution is added to the iron salt solution, which can be added all at once or in batches, preferably in batches.
[0022] In the method of the present invention, the separation in step (2) can be carried out by natural sedimentation, centrifugation, vacuum filtration or filter press to separate the washed suspension into solid and liquid to obtain a solid phase.
[0023] In the method of the present invention, the degree of washing and filtering in step (2) must satisfy the requirement that the mass content of sodium in the catalyst composition obtained finally, calculated as Na2O, is less than 0.2%, preferably the Na2O content is less than 0.15%; and deionized water is used for the washing operation.
[0024] In the method of the present invention, the water content of the wet hydrated iron oxide with a certain water content in step (2) is defined as follows: 1 gram of sample is placed in a 120° C. forced air oven for 12 hours, and the ratio of the difference in mass before and after drying to the mass after drying is defined as the water content of the wet hydrated iron oxide.
[0025] In the method of the present invention, the clay described in step (3) includes kaolin, bentonite and processed derivatives thereof.
[0026] In the method of the present invention, the clay in step (3) is activated before use to remove part of the moisture: drying at 200-300° C. for 12-24 hours.
[0027] In the method of the present invention, the kneading and extruding in step (3) are conventional operation processes.
[0028] In the method of the present invention, the extrusion in step (3) can be carried out by using an extruder or other forming methods, and the shapes of the obtained strip particles include but are not limited to cylindrical, three-leaf clover, four-leaf clover and the like.
[0029] In the method of the present invention, the drying condition in step (3) is drying at 130-250° C. for 6-36 hours. The drying condition is more preferably drying at 140-220° C. for 12-24 hours.
[0030] The invention discloses an application of the para-hydrogen conversion catalyst in the para-hydrogen conversion reaction, wherein the reaction conditions are as follows: the activation condition is vacuum drying at 120-160°C for 12 hours, the evaluation temperature is 77K, and the volume space velocity is 500-2000min -1 , preferably 800~1800min -1 .
[0031] When preparing hydrated iron oxide, the present invention always uses ultrasonic dispersion and physical dispersion in the reaction process, and the dispersion is strengthened from the macroscopic and microscopic synergistic perspective, which can avoid the aggregation of colloids or precipitation to form larger particles, thereby maintaining a highly dispersed state, which is conducive to obtaining smaller reactant particles and improving the specific surface area of the product. The present invention can generate weakly crystalline hydrated iron oxide by micro-area shearing and cavitation formed by ultrasound at room temperature. Experimental studies have found that weak crystallization is conducive to improving catalyst activity. The present invention mixes weakly crystalline hydrated iron oxide with clay in a wet form, at which time the clay can play a certain role as a binder, and also functions as an extrusion molding lubricant, which is conducive to obtaining strip particles with smooth surfaces, having higher strength after drying, and the particles have fewer edges and corners than irregular particles, and low wear. The hydrated iron oxide of the present invention is not dried but mixed with clay in a wet form to reduce energy consumption and improve preparation efficiency. The strip particle catalyst of the present invention can still maintain a high catalytic conversion rate of normal parahydrogen up to 90-98% at high air velocity. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 This is the XRD spectrum of the weakly crystalline hydrated iron oxide obtained in Example 1.
[0033] Figure 2 This is a transmission electron microscope image of the weakly crystalline hydrated iron oxide obtained in Example 1. Implementation
[0034] The present invention is further described in detail below in conjunction with the examples. The Na2O content in the catalyst is tested by XRF method; the hydrated iron oxide (in terms of Fe2O3) content in the catalyst is tested by XRF method. The specific surface area is tested by low-temperature nitrogen adsorption method, and the specific surface area value is calculated according to the BET method; the nanoparticle size and lattice image of iron oxide are observed by transmission electron microscopy. The radial crushing strength of the strip sample is tested according to Chapter 5.11 of the HG / T 3927-2007 method. Abrasion is tested according to HG / T2976-1999. The method for determining the degree of crystallinity of a sample is defined as follows: (1) For a strongly crystalline sample, in its XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is at least one diffraction peak whose ratio is greater than 2, and the half-height width of the diffraction angle 2θ is less than 2º; (2) For a weakly crystalline sample, there is no diffraction peak in its XRD spectrum that meets the above-mentioned strong crystallization determination conditions, but there should be discernible lattice fringes in the high-magnification transmission electron microscope image, or discernible diffraction spots or diffraction rings in the electron diffraction spectrum. The ortho-parahydrogen content is calculated by gas chromatography, and the parahydrogen conversion rate is calculated as: conversion rate = (parahydrogen content% - 25%) / 25.8%, where the ortho-hydrogen and para-hydrogen contents of the raw hydrogen are calculated as 75% and 25% respectively, and the para-hydrogen equilibrium concentration is calculated as 50.8% at liquid nitrogen temperature (77K). Example 1
[0035] Prepare 1.2 mol / L sodium hydroxide solution and 0.5 mol / L ferric chloride solution respectively. At room temperature (25°C), under the conditions of mechanical stirring and ultrasonic dispersion (40kHz, 20W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 2 hours, the suspension is repeatedly washed with water and filtered to remove the sodium ions in the sample to meet the index requirements. The wet hydrated iron oxide (water content 40%) and kaolin activated at 200℃ for 12 hours are kneaded, extruded, and chopped. o C for 12 hours to obtain a cylindrical normal-parahydrogen conversion catalyst.
[0036] The obtained strip-shaped normal-parahydrogen conversion catalyst particles have a radial diameter of 1.0 mm, an axial length of 1.5-2.5 mm, a radial crushing strength of 6.4 N / mm, and a specific surface area of 233 m 2 / g. The mass content of hydrated iron oxide is 85%, and the attrition is 0.18%. The microscopic particle size of hydrated iron oxide is 6.8nm, with weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 2
[0037] Prepare 1.5 mol / L sodium hydroxide solution and 1.0 mol / L ferric chloride solution respectively. At room temperature (30°C), under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (100 kHz, 100 W / L), add a certain amount of ferric chloride solution to the sodium hydroxide solution to meet the OH content in the system. - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 3 hours, the precipitate is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The wet hydrated iron oxide (water content 30%) and kaolin activated at 300℃ for 10 hours are kneaded, extruded, and chopped. o C for 12 hours to obtain a cylindrical normal-parahydrogen conversion catalyst.
[0038] The obtained strip-shaped normal-parahydrogen conversion catalyst particles have a radial size of 1.2 mm, an axial length of 1.5 to 3.0 mm, a radial crushing strength of 5.8 N / mm, and a specific surface area of 202 m 2 / g. The mass content of hydrated iron oxide is 89%, and the attrition is 0.18%. The microscopic particle size of hydrated iron oxide is 6.6nm, with weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 3
[0039] Prepare 1.5 mol / L sodium carbonate solution and 1.0 mol / L ferric chloride solution respectively. At 45°C, under the conditions of mechanical stirring (300 rpm) and ultrasonic dispersion (40 kHz, 100 W / L), add a certain amount of sodium hydroxide solution to the ferric chloride solution to meet the OH - / Fe 3+ The molar ratio is 3.5, and a suspension is formed. After standing for 0.5 hours, the precipitate is repeatedly washed and filtered with water to remove the sodium ions in the sample to meet the index requirements. The wet hydrated iron oxide (water content 25%) and kaolin activated at 300℃ for 6 hours are kneaded, extruded, and chopped. o C for 12 hours to obtain a clover-shaped normal-parahydrogen conversion catalyst.
[0040] The obtained strip-shaped normal-parahydrogen conversion catalyst particles have a radial diameter of 1.5 mm, an axial size of 1.5-4.5 mm, a radial crushing strength of 6.2 N / mm, and a specific surface area of 227 m 2 / g. The mass content of hydrated iron oxide is 92%, and the attrition is 0.19%. The microscopic particle size of hydrated iron oxide is 6.5nm, with weak crystalline state. The normal and para-hydrogen conversion performance test is shown in Table 1. Example 4
[0041] The same as in Example 1, the water content of the wet hydrated iron oxide was changed. When the water content was adjusted to 20%, it was found that the material was too dry and it was difficult to achieve uniform mixing and extrusion molding. When the water content was adjusted to 60%, it was found that a large amount of clay needed to be added to achieve uniform mixing and extrusion molding, and the active component content was too low. Comparative Example 1
[0042] The catalyst was prepared according to the method provided in Example 1, but without adding clay, and it was found that extrusion molding was difficult and the strips were easily broken. The obtained product was crushed into particles with irregular shapes, many edges and corners, and the abrasion was 0.38%. Particles of 30 to 40 mesh were selected for evaluation and testing. The normal-parahydrogen conversion performance test is shown in Table 1. Comparative Example 2
[0043] Iron oxide was prepared according to the method provided in Example 1 of CN202210029537.5. The iron oxide grain size was 23 nm and the crystallinity was high. After testing, its specific surface area was only 66 m 2 / g. It was pressed into 1 mm thick tablets and slightly crushed. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 3
[0044] According to the method provided in Example 1 of CN202111354244.6, iron oxide was prepared. The obtained doped iron oxide had a grain size of 300-1000 nm, and the iron oxide showed strong crystallinity. The tested specific surface area was only 50 m 2 / g. It was pressed into 1 mm thick tablets and slightly crushed. The normal and para hydrogen conversion performance test is shown in Table 1. Comparative Example 4
[0045] According to the research content of the literature [Journal of Research of the National Bureau of Standards, 1958, 60 (3): 221-227], the catalyst obtained in Example 1 was crushed and 30-40 mesh particles were selected. When used for high-space-velocity normal-parahydrogen conversion performance testing, it was found that the pressure drop of the reaction system was large and the hydrogen flow resistance was too large, which was not suitable for high-space-velocity evaluation.
[0046] Table 1 Parahydrogen conversion rate of catalysts
[0047] Test conditions: Activation conditions are vacuum drying at 130°C for 12 hours, and evaluation temperature is 77K.
Claims
1. A strip-shaped normal-parahydrogen conversion catalyst, characterized in that: The invention comprises weakly crystalline hydrated iron oxide and clay, wherein the weakly crystalline hydrated iron oxide accounts for 80% to 95% and the clay accounts for 5% to 20% based on the total weight of the catalyst; the radial size of the catalyst particles is 1.0 to 1.5 mm and the axial length is 1.5 to 4.5 mm; the microscopic particle size of the weakly crystalline hydrated iron oxide is 3 to 12 nm; the weakly crystalline hydrated iron oxide has the following characteristics: (1) in the XRD spectrum, the peak intensity of all characteristic diffraction peaks is compared with the baseline intensity at the position (2θ), and there is no diffraction peak whose ratio is greater than 2 and whose half-height width of the diffraction angle 2θ is less than 2°; (2) there are discernible lattice fringe images in the high-magnification (200,000 times and above) transmission electron microscope images or discernible diffraction spots or diffraction rings in the electron diffraction spectrum.
2. The catalyst according to claim 1, characterized in that: The radial crushing strength is 4.5-12.5N / mm, and the abrasion is 0.10-0.25%. The specific surface area is 150-285m 2 / g.
3. A method for preparing a strip-shaped normal-parahydrogen conversion catalyst according to claim 1 or 2, characterized in that The method comprises the following steps: (1) mixing an iron salt solution and an inorganic alkali solution under the simultaneous action of ultrasonic dispersion and mechanical dispersion to form a colloidal mixture, and then allowing the colloidal mixture to stand for 0.5 to 5 hours; (2) washing and separating the mixture of step (1) to obtain wet hydrated iron oxide having a water content of 25 wt% to 50 wt%; and (3) fully and uniformly mixing the wet hydrated iron oxide obtained in step (2) with clay, kneading, extruding and drying to obtain a strip-shaped normal-parahydrogen conversion catalyst.
4. The method according to claim 3, characterized in that: The iron salt in step (1) is ferric chloride and / or ferric sulfate; the iron salt solution is Fe 3+ The calculated concentration is 0.10 to 1.5 mol / L, preferably 0.15 to 1.0 mol / L.
5. The method according to claim 3, characterized in that: The inorganic alkali in step (1) is one or more of sodium hydroxide, potassium hydroxide, sodium carbonate, sodium bicarbonate or ammonium bicarbonate, preferably sodium hydroxide or potassium hydroxide; the concentration of the inorganic alkali solution is OH - The calculated concentration is 0.5 to 2.0 mol / L, preferably 1.0 to 1.5 mol / L.
6. The method according to claim 3, characterized in that: The iron salt solution in step (1) is Fe 3+ Calculate with inorganic alkali solution to OH - The molar ratio is 3.0 to 4.
5.
7. The method according to claim 3, characterized in that: The ultrasonic dispersion conditions in step (1) are: ultrasonic frequency 20-100 kHz, ultrasonic power density acting on the reaction material is 10-1000 W / L, and ultrasonic temperature is 10-45°C; the preferred conditions for ultrasonic dispersion are: ultrasonic frequency 40-80 kHz, ultrasonic power density 20-100 W / L, and ultrasonic temperature maintained at 20-35°C.
8. The method according to claim 3, characterized in that: The separation in step (2) is carried out by natural sedimentation, centrifugation, vacuum filtration or filter press to separate the washed suspension into solid and liquid to obtain a solid phase.
9. The method according to claim 3, characterized in that: The degree of washing and filtering in step (2) is such that the mass content of sodium in the catalyst composition obtained finally, calculated as Na2O, is less than 0.2%.
10. The method according to claim 3, characterized in that: The clay described in step (3) is activated before use to remove some of the moisture: drying at 200-300° C. for 12-24 hours.
11. The method according to claim 3, characterized in that: The extrusion in step (3) can be carried out by using an extruder or other forming methods, and the obtained strip particles are in the shape of a cylinder, a three-leaf clover, or a four-leaf clover.
12. The method according to claim 3, characterized in that: The drying conditions described in step (3) are drying at 130-250° C. for 6-36 hours.
13. Use of the para-hydrogen conversion catalyst according to claim 1 or 2 in a para-hydrogen conversion reaction, wherein the reaction conditions are: a volume space velocity of 500-2000 min -1 , preferably 800~1800min -1 .
Citation Information
Patent Citations
Supported ortho-parahydrogen conversion catalyst and preparation method thereof
CN112044457A
Orthohydrogen and parahydrogen conversion catalyst for liquid hydrogen conversion and preparation method thereof
CN113797928A
Nano hydrated iron oxide as well as preparation method and application thereof
CN114314677A
Catalyst for catalyzing ortho-parahydrogen conversion as well as preparation method and application of catalyst
CN114367288A
Method for production of para-hydrogen, catalyst for its realization and method for production of catalyst
RU2091294C1